A recent overview on the synthesis of 1,4,5-trisubstituted 1,2,3-triazoles - Shiri, Pezhman; Amani, Ali Mohammad; Mayer-Gall, Thomas (Beilstein Journal of Organic Chemistry, 2021)
Diverse strategies for the efficient and attractive synthesis of a wide variety of relevant 1,4,5-trisubstituted 1,2,3-triazole molecules are reported. The synthesis of this category of diverse fully functionalized 1,2,3-triazoles has become a necessary and unique research subject in modern synthetic organic key transformations in academia, pharmacy, and industry. The current review aims to cover a wide literature survey of numerous synthetic strategies. Recent reports (2017–2021) in the field of 1,4,5-trisubstituted 1,2,3-triazoles are emphasized in this current review.
Keywords: azides; Click reaction; [3 + 2]‐cycloaddition; fully functionalized 1,2,3-triazoles; N-containing heterocycles; 1,4,5-trisubstituted 1,2,3-triazoles